2016
DOI: 10.3847/0004-637x/823/2/128
|View full text |Cite
|
Sign up to set email alerts
|

THE QUEST FOR DUSTY STAR-FORMING GALAXIES AT HIGH REDSHIFT z ≳ 4

Abstract: Far-infrared and submillimeter wavelength surveys have now established the important role of dusty, star-forming galaxies (DSFGs) in the assembly of stellar mass and the evolution of massive galaxies in the Universe. The brightest of these galaxies have infrared luminosities in excess of 10 13 L with implied star-formation rates of thousands of solar masses per year. They represent the most intense starbursts in the Universe, yet many are completely optically obscured. Their easy detection at submm wavelengths… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 160 publications
(230 reference statements)
4
77
0
Order By: Relevance
“…For SFGs with intrinsic SFRṀ ⋆ 30 M ⊙ yr −1 the UV data, even when dust corrected via the UV slope-IRX relationship, strongly underestimate the intrinsic SFR, which is instead better probed by far-IR observations. This is because high SFRs occur primarily within heavily dust-enshrouded molecular clouds, while the UV slope mainly reflects the emission from stars obscured by the diffuse, cirrus dust component (Silva et al 1998;Efstathiou et al 2000;Efstathiou & Rowan-Robinson 2003;Coppin et al 2015;Reddy et al 2015;Mancuso et al 2016a). On the other hand, at low SFRṀ ⋆ 10 M ⊙ yr −1 the dust-corrected UV data efficiently probe the intrinsic SFR.…”
Section: Sfr Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For SFGs with intrinsic SFRṀ ⋆ 30 M ⊙ yr −1 the UV data, even when dust corrected via the UV slope-IRX relationship, strongly underestimate the intrinsic SFR, which is instead better probed by far-IR observations. This is because high SFRs occur primarily within heavily dust-enshrouded molecular clouds, while the UV slope mainly reflects the emission from stars obscured by the diffuse, cirrus dust component (Silva et al 1998;Efstathiou et al 2000;Efstathiou & Rowan-Robinson 2003;Coppin et al 2015;Reddy et al 2015;Mancuso et al 2016a). On the other hand, at low SFRṀ ⋆ 10 M ⊙ yr −1 the dust-corrected UV data efficiently probe the intrinsic SFR.…”
Section: Sfr Functionsmentioning
confidence: 99%
“…Recent wide-area far-IR/(sub-)mm surveys conducted by Herschel, ASTE/AzTEC, APEX/ LABOCA, JCMT/SCUBA2, and ALMA-SPT (e.g., Gruppioni et al 2013;Lapi et al 2011;Weiss et al 2013;Strandet et al 2016;Koprowski et al 2014Koprowski et al , 2016, in many instances eased by gravitational lensing from foreground objects (Negrello et al 2014Nayyeri et al 2016), have revealed an abundant population of dusty star-forming galaxies (SFG) at high redshift z 1, responsible for the bulk of the cosmic star formation history (Mancuso et al 2016a;Lapi et al 2017). Continuity equation arguments have undoubtedly demonstrated that these galaxies constitute the high-redshift progenitors of local ellipticals (Aversa et al 2015;Mancuso et al 2016a,b), and as such the future hosts of the most massive black holes (BHs) in the Universe.…”
Section: Introductionmentioning
confidence: 99%
“…Finkelstein et al (2015a) At face value, our measurements are consistent with those of Durkalec et al (2015) at z ∼ 4 and with those of Finkelstein et al (2015a) at z ∼ 6−7; however, they are inconsistent with those of Harikane et al (2016) over the full range of redshift, and with those of Finkelstein et al (2015a) at z ∼ 4 − 5. Recently Mancuso et al (2016), applying abundance matching to the evolution of the SFR function recovered from UV+far-IR data, found indication for a non-evolving M * /M h ratio at z ≥ 4.…”
Section: Evolution Of M * Hmentioning
confidence: 99%
“…Such achievement has become feasible only recently thanks to wide-area far-IR/sub-mm surveys conducted by Herschel, ASTE/AzTEC, APEX/LABOCA, JCMT/SCUBA2, and ALMA-SPT (e.g., Gruppioni et al 2013Gruppioni et al , 2015Lapi et al 2011;Weiss et al 2013;Strandet et al 2016;Koprowski et al 2014Koprowski et al , 2016, in many instances eased by gravitational lensing from foreground objects (e.g., Negrello et al 2014Negrello et al , 2017Nayyeri et al 2016). In fact, galaxies endowed with star formation ratesṀ ⋆ a few tens M ⊙ yr −1 at redshift z 2 were largely missed by rest-frame optical/UV surveys because of heavy dust obscuration, difficult to correct for with standard techniques based only on UV spectral data (e.g., Bouwens et al 2016Bouwens et al , 2017Mancuso et al 2016a;Pope et al 2017;Ikarashi et al 2017;Simpson et al 2017). High-resolution, follow-up observations of these galaxies in the far-IR/sub-mm/radio band via ground-based interferometers, such as SMA, VLA, PdBI, and recently ALMA, have revealed star formation to occur in a few collapsing clumps distributed over spatial scales smaller than a few kpcs (see Simpson et al 2015;Ikarashi et al 2015;Straatman et al 2015;Spilker et al 2016;Barro et al 2016;Tadaki et al 2017).…”
Section: Introductionmentioning
confidence: 99%